Salmonella enteridis ovarian abscess in a 10-year-old patient in New Caledonia - Case report and review of the literature - Ludivine Legay; Marie-Charlotte Ghiducci; Erick Camus (Elsevier, 2019)
Salmonella ovarian abscesses are rare especially in pre-pubertal patients. We report a case of Salmonella enteridis ovarian abscess in a 10-year-old patient with no medical history who had a favorable outcome after surgical management and effective antibiotic therapy. The challenge in our clinical case was to preserve the ovarian reserve of our patient so as not to cause long-term fertility issues. The review of the literature has allowed us to highlight other cases of Salmonella ovarian abscesses, particularly those causes by Salmonella typhi. Most patients were of childbearing age, and generally presented with an underlying pathology (gastro-intestinal, auto-immune) that may have promoted opportunistic pelvic infections. Alternatively, there was often a preexisting ovarian pathology such as: ovarian cyst, endometrioma, teratoma, or dermoid cyst.